Examining the five-stage e-moderating model: designed and emergent practice in the learning technology profession - Bernard Lisewski; Paul Joyce (Association for Learning Technology, 2003)
This paper highlights the need for learning technologists to establish their 'academic legitimacy' within the complexities of online learning and teaching practice. Frameworks such as the 'five stage e-moderating model' can be useful in developing the knowledge base but there are dangers in them becoming too reified within an increasingly commodified higher education (HE) environment. The paper calls for greater professional reflexivity and contestation within learning technology practice and concludes by inviting the ALT-J readership to engage in a critical debate with regard to these issues.